Comparative Analysis of Transaction Costs, Revenues, and Welfare of Plasma and Self-supporting Oil Palm Farmers in Tulang Bawang Regency - Dyah Aring Hepiana Lestari; Fembriarti Erry Prasmatiwi; R Hanung Ismono (Universitas Muhammadiyah Yogyakarta, 2018)
Transaction costs arise as a result of uncertainty in the transaction environment. Vertical integration of farmers in an institution will reduce uncertainty and will reduce transaction costs. Transaction costs will affect income and will ultimately affect the level of welfare. The objective of this research is to compare the transaction costs, income, and welfare between plasma palm oil farmers and independent palm oil farmers. This research used a quantitative research approach with survey method. The research was conducted in Penawartama and Aji Baru sub district, Tulang Bawang Regency. The research location was chosen purposively with the consideration of sub district are the center of palm oil smallholdings. Data collection techniques were used household survey with simple random sampling. Sample size is 152 farmers consisting of 76 plasma farmers and 76 independent farmers. The transaction costs paid by plasma farmers is smaller thanthose paid by independent farmers. Income per hectare of plasma smallholder is higher than the income of the independent smallholder. Even though, palm oil farmers in Tulang Bawang Regency, both plasma and independent farmers are in the prosperous category.